1994
DOI: 10.2118/25240-pa
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Linear Solvers for Reservoir Simulation: A Generic Approach for Existing and Emerging Computer Architectures

Abstract: Recent architectural advances in the computer industry focus on the numerical solution of intensive flows, such as in oil reservoirs, on several processors simultaneously. Different computer architectures evolved from connection of these processors: shared memory with a few processors, distributed memory with up to a few hundred processors, and massively parallel with several thousand processors. Oil industry researchers are developing efficient techniques to improve hydrocarbon recovery in reservoirs by use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Several tests helped to obtain the optimum parallel decomposition1 16,17,18 . An acceptable parallel efficiency (Fig.…”
Section: Dynamic Modelmentioning
confidence: 99%
“…Several tests helped to obtain the optimum parallel decomposition1 16,17,18 . An acceptable parallel efficiency (Fig.…”
Section: Dynamic Modelmentioning
confidence: 99%
“…Several publications in the literature have dealt with the application of parallel computing to petroleum reservoir simulation in sharedmemory parallel environments. Scott et al (1987) Bhogeswara and Killough (1993) and Cowsar et al (1991Cowsar et al ( , 1992 worked on the parallel solution of linearized finite-difference equations. Mayer (1989) solved the Buckley-Leverett problem on a Thinking-Machines CM-2 machine and showed that the machine can handle large problems as well.…”
Section: Parallel Computingmentioning
confidence: 99%
“…irregular grids, and local grid refinement have only been addressed to a limited extent. 25 The effect of these non-regular data structures will be significant on load balancing as well as single node performance since vectorization will be reduced.…”
Section: Future Issues In Parallelizationmentioning
confidence: 99%